PELATIHAN “SELF AWARENEES” UNTUK MENURUNKAN INTERNAL PERSEPSI MENIKAH DINI - Haq, Akhmad Liana Amrul; Pambuko, Zulfikar Bagus (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to test the effectiveness of self-awareness training to reduce perceptions of early marriage. The subjects in this study were 6 people who were divided into two groups, 3 subjects were in the experimental group (given training) and 3 subjects were in the control group (not given training). . Data collection in this study used the internal scale of perceptions of early marriage and was analyzed using the non-parametric Mann-Whitney U technique. The results of the 2-group differential test using SPSS were Asymp values. Sig of 0.043 (p <0.05), this shows that